2010
DOI: 10.1097/fjc.0b013e3181dab014
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Mutated Cardiac Ion Channels in Inherited Arrhythmia Syndromes

Abstract: Inherited arrhythmia syndromes comprise an increasingly complex group of diseases involving mutations in multiple genes encoding ion channels, ion channel accessory subunits and channel interacting proteins, and various regulatory elements. These mutations serve to disrupt normal electrophysiology in the heart, leading to increased arrhythmogenic risk and death. These diseases have added impact as they often affect young people, sometimes without warning. Although originally thought to alter ion channel functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 90 publications
1
25
0
Order By: Relevance
“…The subtle mutations, as simulated here, would not be expected to significantly modify the structure of the channel. It is also worth mentioning that some I Kr blocking drugs have been shown to modify channel trafficking [37]. In this paper, this effect has not been specifically taken into account, but would be interesting to consider with sufficient data to inform the model in future studies [37].…”
Section: Discussionmentioning
confidence: 99%
“…The subtle mutations, as simulated here, would not be expected to significantly modify the structure of the channel. It is also worth mentioning that some I Kr blocking drugs have been shown to modify channel trafficking [37]. In this paper, this effect has not been specifically taken into account, but would be interesting to consider with sufficient data to inform the model in future studies [37].…”
Section: Discussionmentioning
confidence: 99%
“…Approaches that have been found to increase hERG channel function include low-temperature incubation (Zhou et al, 1999), sarcoplasmic/ER Ca 21 -ATPase inhibition (Delisle et al, 2003), hERG channel blockers (Zhou et al, 1999;Ficker et al, 2002), glycerol (Zhou et al, 1999), small RNA interference targeting dominant negative mutant hERG channels (Lu et al, 2013;Zarzoso and Noujaim, 2013), and intragenic suppression (Delisle et al, 2005). Although these approaches are effective for the rescue of some mutant hERG channels in vitro, most of them are difficult to apply clinically (Balijepalli et al, 2010). In addition, we have previously shown that extracellular K 1 regulates hERG function and its stability in the plasma membrane (Guo et al, 2009;Massaeli et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this finding, different trafficking-deficient mutations in several regions of the hERG channel protein have been identified to cause LQT2 syndrome. Such mutations include; (T65P) in the N-terminus region, (N470D and A561V) in the transmembrane region, (G601S, Y611H, V612L, T613M, and L615V) in the pore region and (R752W, F805C, V822M, R823W, and N861I) in the C terminus 116 . In addition, the missense mutation (A558P) in hERG has been shown to exert a dominant negative effect causing trafficking deficiency of the channel and fever-induced QT interval prolongation in patients 117 .…”
Section: Channelopathies As a Results Of Altered Trafficking In Heart mentioning
confidence: 99%
“…Such SCN5A trafficking-deficient mutations in Brugada syndrome include T351I, R367H, R1232W, R1232W/T1620M, R1432G, and G1743R 116 . Also mutations in Nav1.5 which limit binding of Nav1.5 to a membrane anchor protein ankyrin-G have been shown to cause aberrant Nav1.5 trafficking to the intercalated discs and result in human Brugada syndrome 118 .…”
Section: Channelopathies As a Results Of Altered Trafficking In Heart mentioning
confidence: 99%